PEMODELAN MATEMATIKA ALIRAN DARAH PADA ARTERI KORONER AKIBAT PEMASANGAN STENT - Amirullah, Iqbal; Fatahillah, Arif; Setiawan, Toto Bara (Kadikma, 2019)
Coronary heart disease is a disease caused by accumulation of cholesterol that forms plaques on artery walls for a considerable period of time. Over time, this disease can cause the heart muscle to weaken, and cause complications such as heart failure. One of ways to treat coronary heart disease is the stent installation (rings) or commonly called angioplasty. Angioplasty aims to make the blood vessels narrow to open so that blood flow flows better. The emergence of mathematical modeling as a new science is one alternative to solve these problems. With mathematical modeling, practitioners can make a form of a formula that describes the state of blood flow in the coronary arteries according to actual conditions without ignoring important factors in the system. In this study a mathematical model was built based on the above problems to determine the effectiveness of stent installation or angioplasty in the process that occurs in coronary arteries. Keywords: Coronary heart disease, Mathematical modeling, Stent